(untitled) (Research, Society and Development, 2021)
The relationship between tooth eruption and the appearance of local and general manifestations in children has been a controversial subject in the medical and dental environment with regard to child health. The search aims to verify the association between local and systemic manifestations and the period of eruption of primary dentition in children aged 4 months to 4 years, accompanied by the Oral Health Team of the Family Health Strategy of the municipality of São Gonçalo do Amarante / RN. 55 mothers were interviewed through a questionnaire containing objective questions about general identification data and about signs and symptoms related to tooth eruption. The results lower than 75% of the children analyzed symptoms during the eruption of the deciduous dental elements and the most reported symptoms were increased salivation, fever and diarrhea. The greatest symptomatology (62%) was between 4 months and 1 year old. Regarding the conduct in the face of symptoms, 44% of the interviewees reported that they only follow the evolution, without looking for a dentist. It is concluded, therefore, that during the eruption of deciduous teeth, local and / or systemic manifestations are perceived by those responsible, especially before the child’s first year of life.